South-South Cooperation : How Mongolia Learned from Chile on Managing a Mineral-Rich Economy - van den Brink, Rogier (World Bank, Washington, DC, 2014)
Mongolia's mineral-rich economy was hit extremely hard by the global downturn during 2008-9, when copper prices plunged, external demand fell, and growth collapsed. The shock exposed serious underlying weaknesses in the management of the country's natural resource wealth, particularly the lack of policies to insulate the economy from commodity cycles and real exchange rate appreciation pressures, an inadequate safety net, and poor public investment planning. These issues gained further urgency with the signing of a major copper mining deal in 2009 that further increased the country's mineral dependence. As part of its reform efforts and with the assistance of the World Bank and the International Monetary Fund (IMF), the government began an intensive south-south exchange, notably with Chile, another major copper producer, on strengthening the policy environment. The dialogue proved critical in the passage of several landmark laws within the space of a few years, including a fiscal stability law modeled after Chile, and the accompanying integrated budget and procurement and social welfare laws. These reforms will be crucial in managing the boom-bust cycle of mineral prices and mitigating Dutch disease effects by anchoring a prudent countercyclical fiscal policy, strengthening public financial management, increasing savings, and providing a fiscally sustainable social safety net targeted to the poor.